"Ahora que somos otros": notas en torno a la "otredad optada" y al rock juvenil costarricense - Zúñiga Núñez, Mario (2023)
This paper analyzes in depth the subject of the “otherness” in the heart of western society. Initially it explores, from a theoretical point of view, the vision that the occidental society is unique and homogeneous, as well as the objections by groups of “others” (e.g. working class, women, and youth) to this way of understanding society. Then, it explores juvenile otherness, through which the esthetic dissidences conformed by youth counter and sub culture has proposed ideas that are conflictive with the adult and homogeneous perspective. Lastly we give special emphasis on the esthetic manifestations of Costa Rican youth rock bands.